Buddhism - Ellinger, Herbert (London : SCM Press LTD, 1995)
Presents the story of Buddhism's origins and growth through the centuries, discussing its basic philosophy and the evolution of the three major schools of Buddhist thought
Introduction: The Modern Buddhist world -- The Life of the Buddha -- The Spread of Buddhism -- The Varieties of Buddhism -- The Literature of Buddhism -- The Arts and Buddhism -- The Year in Buddhism -- Buddhism today
Includes bibliographical references and index
Keywords: Buddhism -- Juvenile literature; Buddhism